RANCANG BANGUN SISTEM KONTROL MOTOR LISTRIK BERBASIS RASPBERRY PI - Ali Abrar; Syaeful Akbar; Tukino Tukino (LPPM Universitas Putera Batam, 2023)
This study will develop and execute control of DC motors and servo motors on a 4WD robot controlled by a keypad and equipped with grippers and a USB webcam to broadcast video so that the gripper robot vehicle can view items in front of it. Control actions were implemented using Python-based user defined programming on a Raspberry Pi 4 with motor driver controller. The challenge described in this article is how to optimize a tool design utilizing a driver loaded directly on an SBC. The goal of this study is to create technical ideas in the area of electric motor control and mechatronics in the form of applications. The design, production, and testing stages are followed utilizing the Raspberry Pi, RPi Motor Driver Board, and Python as the major components. The study's findings include a prototype wheeled robot with a camera for image capture and an actuator in the form of a servo motor with a gripper/clamp as an attachment. The study's conclusion is that the design outcomes of electric motor control utilizing Raspberry Pi-based can perform more efficiently.